Selective targeting of α7 nicotinic acetylcholine receptor by synthetic peptide mimicking loop I of human SLURP-1 provides efficient and prolonged therapy of epidermoid carcinoma in vivo - Shlepova, O. V.; Shulepko, M. A.; Shipunova, V. O.; Bychkov, M. L.; Kukushkin, I. D.; Chulina, I. A.; Azev, V. N.; Shramova, E. I.; Kazakov, V. A.; Ismailova, A. M.; Palikova, Y. A.; Palikov, V. A.; et al. (Frontiers in Cell and Developmental Biology, 2023)
This is a provisional file, not the final typeset article α7-Type nicotinic acetylcholine receptor (α7-nAChR) promotes the growth and metastasis of solid tumors. Secreted Ly6/uPAR-Related Protein 1 (SLURP-1) is a specific negative modulator of α7-nAChR produced by epithelial cells. Here, we investigated mechanisms of antiproliferative activity of recombinant SLURP-1 in epidermoid carcinoma A431 cells and activity of SLURP-1 and synthetic 21 a.a. peptide mimicking its loop I (Oncotag) in a xenograft mice model of epidermoid carcinoma. SLURP-1 inhibited the mitogenic pathways and transcription factors in A431 cells, and its antiproliferative activity depended on α7-nAChR. Intravenous treatment of mice with SLURP-1 or Oncotag for 10 days suppressed the tumor growth and metastasis and induced sustained changes in gene and microRNA expression in the tumors. Both SLURP-1 and Oncotag demonstrated no acute toxicity. Surprisingly, Oncotag led to a longer suppression of pro-oncogenic signaling and downregulated expression of pro-oncogenic miR-221 and up-regulated expression of KLF4 protein responsible for control of cell differentiation. Affinity purification revealed SLURP-1 interactions with both α7-nAChR and EGFR and selective Oncotag interaction with α7-nAChR. Thus, the selective inhibition of α7-nAChRs by drugs based on Oncotag may be a promising strategy for cancer therapy.